Transformasi Diri: Pengembangan Karakter Langkah Menuju Pemulihan Narapidana Perempuan di LP Tanjung Gusta. Medan - Hek, Tan Kim; Mipo, Mipo; Hou, Amin; Sukiman, Sukiman; Gani, Petrus (Lembaga Dongan Dosen, 2025)
Sosialisasi